Sunscreen Activity Test on Iler Leaf Ethanol Extract Cream (Coleus Scutellarioides (L) Benth) In Vivo - Zalza Zalzabila Adelya Putri; Endah Widhihastuti (Journal of Science and Technology Research for Pharmacy, 2023)
Indonesia is one of the countries known as a tropical climate country with a high intensity of sun exposure. The sun's UV rays have health benefits. However, UV rays also have negative effects on skin health. Therefore, additional protection against solar UV rays is needed, namely by using sunscreen preparations derived from Iler Leaves (Coleus scutellarioides (L) Benth) which contain flavonoid and phenolic compounds. The purpose of this study was to determine the most optimal ethanol extract cream formula of iler leaf (Coleus scutellarioides (L) Benth) after preparation evaluation and determine the sunscreen activity of iler leaf ethanol extract cream (Coleus scutellarioides (L) Benth) in vivo. This research is a real pure experiment or also called True Experimental Research and uses The post test Only Control Group Design method. The results obtained from the evaluation of the ethanol extract of iler leaf cream preparation formula are with a cream formula consisting of 1.5% iler leaf extract, 18% stearic acid, 2% TEA, 2% cetyl alcohol, 8% glycerin, 0.2% metal paraben, 0.02% propyl paraben and aquadest. And after in vivo testing on white rats, it was found that the ethanol extract cream preparation of iler leaves had sunscreen activity as evidenced by the erythema effect that appeared after exposure under sunlight. So it can be concluded that the most optimum cream formula is a formula containing 18% stearic acid and 2% TEA. And the iler leaf ethanol extract cream has sunscreen activity after in vivo testing.